THE ROLE OF ASEAN IN FACING THE FOURTH INDUSTRIAL REVOLUTION (CASE STUDY: EDUCATION DISPARITY BETWEEN SINGAPORE AND INDONESIA) - Wening Noor Aida Rahmawati (Jurusan Ilmu Hubungan Internasional, 2021)
Industry 4.0 provides opportunities and threats to life, such as income inequality, nature destruction, cybercrime, and internet dependence. Threats also occur in the education field. In 2019, a social media platform called ‘we are social’ published a study revealing that the average person spends six hours a day using the internet. Four out of ten ASEAN member countries are included in the top ten social media user countries. Indonesia is one of the countries belonging to this category. Similarly, Singapore also has a relatively high level of social media use. However, its conditions tend to be stable, making it easier for Singapore to overcome those problems. On the other hand, with a larger population, it is more difficult to control such problems in Indonesia. ASEAN, an international organization, strives to reduce disparities between Singapore and Indonesia through joint integration between its member countries. In this paper, the author explains about ASEAN businesses in facing disparities in the region, especially concerning industrial readiness 4.0. The author utilized the theory of international organizations and the human development index concept to analyze the case study.